2018
DOI: 10.1073/pnas.1720898115
|View full text |Cite
|
Sign up to set email alerts
|

Methane in groundwater before, during, and after hydraulic fracturing of the Marcellus Shale

Abstract: SignificanceThis study incorporates time series sampling of groundwater before, during, and after drilling, hydraulic fracturing, and initiation of shale gas production. Using monitoring wells installed next to gas well pads and above gas well laterals, previously undocumented responses to drilling and a gas well casing breach were observed, although groundwater impacts arising from the process of hydraulic fracturing were not detected. We discover considerable temporal variability in methane concentrations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 37 publications
2
42
0
Order By: Relevance
“…Concentrations above atmospheric equilibrium were not observed in any of the samples (57), indicating that gas from the Marcellus Formation is not actively entering the streams within 1 km of the sampling points and suggesting that the study streams are not being influenced by faulty well casings. These findings are consistent with those of Barth-Naftilan et al (81), which reported no changes in groundwater methane concentrations that could be linked to shale gas development.…”
Section: Resultssupporting
confidence: 93%
“…Concentrations above atmospheric equilibrium were not observed in any of the samples (57), indicating that gas from the Marcellus Formation is not actively entering the streams within 1 km of the sampling points and suggesting that the study streams are not being influenced by faulty well casings. These findings are consistent with those of Barth-Naftilan et al (81), which reported no changes in groundwater methane concentrations that could be linked to shale gas development.…”
Section: Resultssupporting
confidence: 93%
“…Our data suggests that a large vertical separation exists between unconventional gas production and water wells where thermogenic gas is the target of hydraulic fracturing (e.g. Marcellus Shale; Appalachian Basin) [46][47][48][49]. The situation is markedly different in the Michigan Basin, where biogenic gas is present in the Antrim Shale along the basin margins [50].…”
Section: Vertical Separation Of Water Wells and Hydrocarbon Productionmentioning
confidence: 81%
“…It is important to note that CH 4 and heavier hydrocarbon concentrations in aquifers can vary markedly over time, depth, and distance due to transport, microbial, and oxidative attenuation of natural gas plumes, and activities that are unrelated to HVHF associated with oil and gas production. 61,62 Changes to atmospheric or hydrostatic pressure (e.g., drought) and other disturbance (e.g., groundwater pumping) can impact relative concentrations of hydrocarbons. 14,47,54 Therefore, it is important to undertake appropriate spatiotemporal sampling to monitor CH 4 (and other tracers) in HVHF areas.…”
Section: Established Techniques For Tracing Contaminationmentioning
confidence: 99%